SAT-136 Investigation of Glycemic State among Responders to Hepatitis C Treatment - Elamir, Yasmine (J Endocr Soc, 2019)
Recently, Human Immunodeficiency Virus (HIV)/Hepatitis C (HCV) co-infected persons were reported to have an increased incidence of insulin resistance and lipodystrophy when compared to mono-infected persons. There are multiple randomized multi centered clinical trials that have found that HIV/HCV co-infected persons had a higher risk for diabetes compared to HIV mono-infected subjects even when adjusted for BMI and family history of diabetes. Our aim was to do retrospective analysis to evaluate the changes in the glycemic state following HCV based treatment regimens in patients co-infected with HIV/HCV. Several well published studies show improvement in glycemic control after treatment of HCV. However, after a thorough review of the literature, we did not find any publication examining the effects on glycemic control after treating HCV in those co-infected with HCV/HIV. The purpose of this study is to see if treating HCV in co-infected patients will yield comparable results in improving glycemic control and decreased insulin resistance as other studies have in in treating HCV mono-infection. We observed and analyzed changes in fasting plasma glucose (FPG) and HbA1c levels in 57 patients co-infected with HIV/HCV after achievement of sustained viral response at 12 weeks (SVR 12) that met our inclusion and exclusion criteria. We used FPG and HbA1c levels as our primary end points. We considered improvement of the glycemic state as a decrease of FPG by at least 20 mg/dL (1.1mmol/L) and HbA1c 0.5% when compared to baseline values or reduction of hypoglycemic drugs dosing after HCV had been treated.We found there was no significant difference of FPG and HbA1c from baseline to follow up. There were significant improvements in AST and ALT levels. These findings were not dependent on BMI levels or baseline fibrosure scores. Our patients were all on protease inhibitors which are known to be associated with peripheral insulin resistance and impaired glucose tolerance which could have contributed to the fact that our patients did not have statistically significant improvement of glycemic control after achieving SVR 12. We plan to complete a prospective trial of those mono-infected with HCV in the future.